PENGELOLAAN KEUANGAN PEDESAAN DALAM MENDORONG PEMBANGUNAN WILAYAH PEDESAAN: SUATU TINJAUAN TEORITIS - Azwardi Azwardi; Abu Kosim (Department of Development Economics, Universitas Sriwijaya, 2007)
This research is directed to explain Fiscal Desentralisation theory which is completed with the impact of given transfer to economics connected to APB Desa. The research used Qualitative Descriptif Approach in order to explain the fenomena. Theorically dropping fund to villages will improve development activity but the realization is not significant. It happened because the dropping was only used for routine activities, so many activities which are able to improve economics activities are not done yet, weakness of BPD.In addition, Kades is still having limited abilities in managing the finance, examples: Planning, Budgetting, actuating, controlling and auditing. Key Words : Managing Finance, Fiscal Decentralisation, Country Empowerment Division